Culture Moderates the Genetic and Environmental Etiologies of Parenting: A Cultural Behavior Genetic Approach. (July 2013) - Shikishima, Chizuru; Hiraishi, Kai; Yamagata, Shinji; Neiderhiser, Jenae M.; Ando, Juko
A cultural behavior genetic approach was introduced as a prospective means to describe psychological differences between cultures. We compared genetic and environmental influences on remembered parenting for samples of twins from Japan and Sweden. Data were collected from 720 pairs of young adult Japanese twins and 824 pairs of adult Swedish twins using the Parental Bonding Instrument. In both samples, a very similar phenotypic factor structure was developed for maternal and paternal parenting. However, the genetic and environmental contributions were different. Parenting in Japan showed more genetic influences, whereas parenting in Sweden showed more shared environmental influences. Moreover, covariation among the six dimensions of parenting (i.e., maternal and paternal Warmth, Protectiveness, and Authoritarianism) was due to genetic correlations in Japan and to shared environmental correlations in Sweden. These results are consistent with the cultural psychology argument that parenting practices are child centered in Japan but parent centered in the West.